O078 Why do patients decline to participate in clinical trials? The view of potential participants having varicose vein treatments. (22nd July 2022) - Sharma, A; Belramman, A; Bootun, R; Lane, T R A; Davies, A H
Abstract: Introduction: Varicose veins are prevalent throughout the UK population, affecting a third of adults. Various treatments exist and must be validated by rigorous testing. Randomised control trials (RCTs) are the accepted gold standard in the hierarchy of evidence, comparing the effectiveness of interventions. Poor recruitment is common among surgical trials and threatens their success. To ensure adequate participation, the underlying barriers to recruitment need to be identified. The objective of this study was to identify the reasons for refusal in four varicose vein RCTs. Secondary aims analysed patient characteristics to assess patient trends. Methods: A qualitative survey was offered to eligible patients refusing recruitment, recording their reasons. Patients were identified and given an information leaflet before confirming a decision. Patient characteristics, demographics and themes were assessed using qualitative and statistical analysis. Ethical approval was not required. Results: Overall, 115/429 of patients refused RCT participation and all ( n =115) completed the survey. Patients mainly expressed refusal due to preferences for different treatments (25%) followed by employment commitments (14%). Follow-up procedures dissuade patients and anxiety was associated with patient characteristics. Females are more concerned about their autonomy (26.4%) whereas males express worry about external obligations (14.6%). Misunderstanding the severity of risks of treatments and varicose veins elevated concerns across both genders. Conclusion: Unwillingness to participate is determined by individual circumstances, patient bias and altruism. Multiple factors influence decision making such as familial views and personal demographics. Creating a more robust recruitment process relies on encouraging the acceptance of clinical equipoise and targeting patient beliefs through enhanced communication and improving accessibility. Take-home message: Patients undergoing recruitment into surgical trials are influenced by their ability to understand and recall information, patient preference and individual characteristics which are influenced by demographics such as anxiety and employment. Targeting these identified barriers to participation will improve accessibility into RCTs.